2014
DOI: 10.1063/1.4895041
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin frequency shift hopping in polymer optical fiber

Abstract: We investigated the Brillouin gain spectrum dependence on large strain of up to 60% in a polymer optical fiber (POF) at 1.55 μm, and found that the Brillouin frequency shift (BFS) abruptly changes from ∼2.7 GHz to ∼3.2 GHz. We named this phenomenon “BFS hopping,” and found it to originate from the varied acoustic velocity induced by the stepwise change in the core diameter of the POF. This is because of the yielding of the overcladding layer composed of polycarbonate. After the occurrence of BFS hopping phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…As for problem (1) mentioned above, the Stokes light can be stably returned from the POF through the interface between the POF and the silica single-mode fiber (SMF); this structure is simpler and more robust than that previously reported [14]. As for problem (2), the BFS in the POF can be irreversibly upshifted by ~300 MHz only by applying large strain (named BFS hopping [21]). A distributed measurement is experimentally demonstrated, in which a 0.46-m-long heated POF section is successfully detected.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…As for problem (1) mentioned above, the Stokes light can be stably returned from the POF through the interface between the POF and the silica single-mode fiber (SMF); this structure is simpler and more robust than that previously reported [14]. As for problem (2), the BFS in the POF can be irreversibly upshifted by ~300 MHz only by applying large strain (named BFS hopping [21]). A distributed measurement is experimentally demonstrated, in which a 0.46-m-long heated POF section is successfully detected.…”
Section: Introductionmentioning
confidence: 92%
“…Then, a partial reflection point can be automatically created at the butt-coupled interface between the POF and the silica SMF (the pigtail of an optical circulator) [15], at which Fresnel-reflected light with a reflectivity of 0.2% (calculated The key to the solution of the second problem is the BFS hopping phenomenon [21], in which the BFS in the POF (BFS: ~2.8 GHz) can be irreversibly upshifted by ~300 MHz only by applying a large strain of >7.3%. Unless cryogenic sensing is the intended application, the BFS "upshift" is preferable because the BFS in a POF decreases with increasing applied strain [16] and temperature [16], [17]).…”
Section: Principlesmentioning
confidence: 99%
“…Thus, at the early stage of research, Brillouin scattering in POFs was expected to be useful in measuring large strains. However, as the large-strain dependence of the BFS [21] was further studied, it was found that, by applying strain of larger than ~5%, a POF locally starts to become slim with a constant outer diameter [26]. With increasing strain up to >60%, the slimmed section spreads along the whole length of the POF.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle this problem, strain and temperature sensors using polymer optical fibers (POFs) [11] have attracted a lot of attention, because POFs are so flexible that they can withstand larger strain of several tens of percent (even 100% [12]). To date, various strain and temperature sensors using POFs have been developed, including those based on fiber Bragg gratings [13,14], modal interference [15][16][17], Brillouin scattering [18][19][20][21][22][23][24][25], and Rayleigh scattering [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…One of the unique features of POF-based strain sensors is what we call a "strain memory effect" [12,19,20,26,27], with which POFs themselves store the information (magnitude and location) of applied large strain even after the strain is released. This nature is caused by plastic deformation of the polymer materials.…”
Section: Introductionmentioning
confidence: 99%